Silver: A morally good money - Guzelian, Christopher P. (REVISTA PROCESOS DE MERCADO, 2018)
It is sometimes said, «money is at the root of all evil.»1 This essay examines whether there are any forms of money (and monetary systems) that are potentially morally good. To do so requires us to look at God’s ethics regarding material resources, and then to see what part, if any, God intends money to serve in the human econ- omy. I conclude that there exists at least one form of money, namely silver, that if used in accord with God’s material resource ethics, is morally good money. God intends the global human economy to be dynamically undergirded by two core principles: sharing resources morally and sustaining the Earth’s environment for future generations and their economic activities. The two principles interrelate and affect the extent and character of each other. They are also intensely ethical concepts, but simultaneously factual. As such, I refer to them throughout this article as «factual-ethical princi- ples.» Both derive directly from the Bible — both the Hebrew and New Testaments. While, as I shall later show, many people are able to disregard one or the other, or both, of these principles in the short run, the principles’ economic gravitas and implications cannot be ignored over the long run. In order to balance the basic sustainment of all human life and to afford wealth and comfort to maximally many members of society, a healthy tension between the two poles must remain in place. From the outset, it is important to describe with some detail aspects of the two principles, and the factual and normative rela- tionship between them. Once these principles are well-de- scribed, it is possible to understand what moral money and monetary systems should look like. Thus, Section 2 describes the first godly factual-ethical principle: moral sharing of resources. Section 3 describes the second godly factual-ethical principle: sustaining the earth. Section 4 combines these principles with a review of the historical monetary system that God  instructed the ancient Israelites to create, as well as Jesus’s reflections on that system, to reach conclusions about whether any form of moral money exists, in spite of oft-heard sentiments that all money is an evil. What must also be said is that this article starts out from the position that the Judeo-Christian portrayal of reality is correct. Apart from beliefs, sentiments, fashions, or faiths that argue to the contrary, ethical values as descended from the teachings and tradi- tions of Jesus of Nazareth and his disciples, and the Holy Scrip- tures, are True. Individual or collective departures from those values and teachings have actual economic implications in the mortal world, the grace and mercy of God notwithstanding (North 1992). I therefore assume for present purposes and this readership that I may refer to Scriptures or Church teachings as incontrovert- ible Truth for what might be considered by non-adherents to be either circular logic or teleological bias.